Acquired alterity : migration, identity, and literary nationalism - Mack, Edward Thomas (New interventions in Japanese studies, 2022)
"A free open access ebook is available upon publication. Learn more at www.luminosoa.org. This is the first monograph-length study in English of the Japanese-language literary activities-both reading and writing-of Japanese migrants to Brazil. It provides a detailed history of Japanese-language bookstores, serialized newspaper fiction, original creative works, and critical apparatuses that existed in Brazil prior to World War II, all contextualized within a history of the first decades of that migration. While functioning in part as an introduction to this community and its literature, the book explores issues related to the politics of critiquing literary texts collectively, a logical move that is at the core of many literary studies today. Acquired Alterity presents a case study of one substantial diasporic population and the self-representations of a number of its members, while at the same time providing a challenge to a dominant mode of literary study, in which texts are often explicitly or implicitly understood through a framework of ethno-nationalism. These subjects reveal the logical flaws in this framework through what Edward Mack is calling their "acquired alterity," the process by which their presumed innate identity is challenged, and the subjects become other to the systems they had conceived themselves as belonging to. The book prompts a reconsideration of the ramifications (and motivations) of literary and cultural analyses of collections of texts and the peoplehood constructs that are often the true objects of that knowledge production"--